1993
DOI: 10.1083/jcb.120.6.1501
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that activation of platelet calpain is induced as a consequence of binding of adhesive ligand to the integrin, glycoprotein IIb-IIIa.

Abstract: Abstract. Calpain (a Ca2+-dependent protease) is present in many cell types. Because it is present in the cytosol, the potential exists that it may regulate critical intracellular events by inducing crucial proteolytic cleavages. However, the concentrations of Ca 2 § required to activate calpain are higher than those attained in the cytoplasm of most cells. Thus, the physiological importance of calpain and the mechanisms involved in its activation have remained elusive. In this study, we show that calpain rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
2
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 44 publications
7
123
2
2
Order By: Relevance
“…8), established that this peptide is cleaved at a site identical to that of the native αII spectrin heterotetramer (Table I). Calpain did not appreciably digest peptides GST-αII [13][14][15][16][17][18] and GST-αII 18-C (data not shown). Calpain digestion of GST-βII 8-CΔ , a fusion peptide encompassing βII spectrin repeat units 8 to 17 and a portion of domain III (58), yielded four cleavage fragments at ≈ 92, ≈ 88, ≈ 70, and ≈ 47 kD (Figure 3).…”
Section: Recombinant Spectrin Peptides Are Cleaved By Calpain At the mentioning
confidence: 91%
“…8), established that this peptide is cleaved at a site identical to that of the native αII spectrin heterotetramer (Table I). Calpain did not appreciably digest peptides GST-αII [13][14][15][16][17][18] and GST-αII 18-C (data not shown). Calpain digestion of GST-βII 8-CΔ , a fusion peptide encompassing βII spectrin repeat units 8 to 17 and a portion of domain III (58), yielded four cleavage fragments at ≈ 92, ≈ 88, ≈ 70, and ≈ 47 kD (Figure 3).…”
Section: Recombinant Spectrin Peptides Are Cleaved By Calpain At the mentioning
confidence: 91%
“…Association of PMCA with the Platelet Membrane Cytoskeleton-Most of the cytoplasmic actin filaments in unstimulated platelets are aggregated into large complexes that sediment from TX100-lysed platelets at 16,000 ϫ g (low speed pellet) (19). However, the membrane-associated skeletal fragments and associated proteins such as integrin ␣ IIb ␤ 3 , spectrin, vinculin, and p60src require 100,000 ϫ g for sedimentation from TX100-lysed unstimulated platelets (high speed pellet) (20).…”
Section: Resultsmentioning
confidence: 99%
“…Thus it is the more active, less phosphorylated form that associates with the cytoplasmic cytoskeleton. This implies that the purpose of redistribution of PMCA is to direct the active Ca 2ϩ pump to specific locations in the activated platelet, possibly to reduce intracellular Ca 2ϩ in focal contact regions thus preventing proteolytic degradation by the Ca 2ϩ -activated proteinase calpain (19). The concomitant inhibition of the pump not associated with the cytoskeleton by tyrosine phos- FIG.…”
Section: Plasma Membrane Ca 2ϩ -Atpase Binding To Platelet Cytoskeletonmentioning
confidence: 99%
“…Work on platelets has shown that the cysteine protease, calpain, is one of the signaling molecules activated following integrin-ligand interactions (35), suggesting it may modulate intracellular events required for effective adhesion. Once activated, calpain can selectively cleave a variety of substrates, many of which are membrane and cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 99%